The Political Dynamics of Islamophobia in Jokowi’s Era: A Discourse Analysis of Online Media Reporting - Irawan, Bambang; Nasution, Ismail Fahmi Arrauf (Studia Islamika, 2021)
This article investigates the online media reporting of Islamophobic policies during the presidency of Joko Widodo, Indonesia’s current president. The study comprises a critical discourse analysis, which identifies three reporting dimensions, namely micro, mezzo, and macro. The article finds that discriminatory policies against Indonesian Muslims have triggered the emergence of news of Islamophobia in government policies. Politically, this causes Islamophobic propaganda, which, for the government, is a form of discourse struggle, the aim of which is to secure public support. Reports of government-backed Islamophobic propaganda moved the government to amend some of its policies, and facilitated the emergence of counter-narrative news, which refuted these accusations of Islamophobia. This study also shows that accusations of Islamophobia against the government are a result of the trauma many Muslims experienced, historically, long before the Jokowi presidency.